Carbapenem-sparing strategy: carbapenemase, treatment, and stewardship. Issue 6 (December 2019) - Corcione, Silvia; Lupia, Tommaso; Maraolo, Alberto Enrico; Mornese Pinna, Simone; Gentile, Ivan; De Rosa, Francesco G.
Abstract : Purpose of review: describing the current role of carbapenems and carbapenem-sparing strategies in the setting of antimicrobial stewardship programs. Recent findings: sparing carbapenems with other drugs appears to be an interesting perspective for a variety of reasons in the current context of the multidrug-resistant (MDR) pandemic. Specific algorithms should also be precisely investigated to define better how to spare carbapenems within empiric and targeted regimens, with combination treatment or monotherapies, aiming at the best use of the new drugs and improving de-escalation as soon as possible for most of the patients. Summary: stewardship programs may be useful in reducing probable misuse and overuse of antibiotics, which has probably contributed to the emergence of carbapenem-resistant bacteria worldwide. The proposal of carbapenem-sparing strategies has then generated substantial scientific debate and, overall, the concept of sparing these drugs is well advocated together with judicious use of novel drugs, appropriate measures of infection control and prevention as well as in stewardship programs to curb the spread of MDR and XDR-strains in healthcare facilities.